El referéndum contra el status quo Análisis de Ecuador, Venezuela, Perú y Bolivia - Welp, Yanina (Diálogos Latinoamericanos, 2009)
In Latin America, the referendum has become a subject of controversy from experiences such as those promoted by Alberto Fujimori in Peru, Hugo Chávez in Venezuela, Evo Morales in Bolivia and Rafael Correa in Ecuador. The discussion of its results has polarized a debate between those who argue that direct consultation to citizenry promotes a deepening of democracy and those who warn against populism and / or the accumulation of power. Seeking to contribute to this debate, the article explores the conditions under which a referendum has been called in those cases and their consequences. The findings of the study emphasizes that the referendum has served to channel an existing conflict, which manifests itself as soon as a leader outside the hegemonic groups gets the power. However, direct democracy is not in itself but the tension between ideological polarization and the willingness of actors to accept the 'rules of the game' which determines the outcome of these practices in the long term.